Innovation With Strengths: A Collaborative Approach to PhD/DNP Integration in Doctoral Education. Issue 5 (September 2018) - Lusk, Marcie Dianne; Marzilli, Colleen
Abstract : Abstract: Doctorally prepared nurses are well equipped to provide solutions to complex issues in today's rapidly changing health care environment. Collaborative relationships between doctor of nursing practice (DNP)- and doctor of philosophy (PhD)-prepared nurses facilitate timely translation of research into practice, enhanced educational opportunities, and development of interventions to improve health outcomes; however, challenges have been identified that hinder collaboration. This article highlights a three-pronged innovative and structured approach to identify individual student strengths, facilitate collaboration among DNP and PhD students, and set the foundation for implementation of a strengths-based curriculum during the doctoral educational experience.